The family dynamics of COVID-19 survivors: the perspectives of parents and their children - Qur'aniati, Nuzul; Ilya Krisnana; Erina Putri, Dwi Adven; Handasari, Mutiara (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the family dynamics of coronavirus disease-2019 survivors from the perspective of parents and children. Method: The descriptive, qualitative study was conducted from May 27 to December 7, 2021, in Surabaya, East Java, Indonesia, and comprised parents and children of individuals who survived a coronavirus disease-2019 infection. Data was collected through in-depth interviews. Data was analysed using thematic analysis. Results: Of the 18 subjects, 10(55.5%) were parents and 8(44.5%) were children of the survivors. Among the parents, 4(40%) were aged 30-40 years and 6(60%) were aged >40 years, while among the children, 6(75%) were aged 7-12 years and 2(25%) were aged 12-18 years. The three themes identified were factors shaping family response, response and problem-solving, and requiring care and social support. Conclusion: Coronavirus disease-2019 patients, in addition to medical support need psychosocial support for better health outcomes. Keywords: Psychosocial, COVID-19, Adaptation, Psychological, Social problems, Health.